Silicon-tin composite material, preparation method and application thereof and lithium ion battery
By using silicon-tin composite material with core-shell structure in lithium-ion batteries, the problems of large volume changes, poor mechanical strength and high charge transfer resistance are solved, efficient cycling and rate performance are achieved, and the electrochemical performance of the battery is improved. .
Patent Information
- Application Number
- CN202411412466.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-10
AI Technical Summary
The existing silicon-tin composite materials have problems such as large volume changes, poor mechanical strength and high charge transfer resistance in lithium-ion batteries, resulting in insufficient cycling performance, capacity and rate performance.
Si-tin composite material adopts a core-shell structure, where the core includes silicon material and tin nanoparticles, the inner and outer carbon layer is coated with carbon layer, and the outer carbon layer is a chestnut-shaped carbon layer, and heteroatoms are doped in the carbon layer, passing through plasma Preparation by auxiliary ball milling and solvent gel method.
It realizes silicon-tin composite materials with small volume changes, high mechanical strength and low charge transfer resistance, which can take into account excellent cycling performance, capacity and rate performance, and improves the electrochemical performance of lithium-ion batteries.
Smart Images

Figure CN119297237A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silicon-tin composite material, a preparation method thereof, an application thereof and a lithium ion battery. Background Art
[0002] In the face of the global energy crisis, the demand for new energy has become increasingly urgent due to the depletion of oil resources and the growing demand for energy in emerging industries. As a promising secondary battery, lithium-ion batteries have received considerable attention, especially lithium-ion batteries are widely used in new energy vehicles, portable electronic devices, aerospace equipment and other fields. However, the capacity of lithium is limited by the electrode material, especially as the main negative electrode material in commercial applications. The current theoretical specific capacity of graphite is only 372mAh / g, which has reached the maximum commercialization. In order to obtain battery performance with higher energy density and high rate performance, silicon-based and tin-based materials are considered to be the most promising negative electrode materials to replace graphite. The theoretical capacity of silicon and tin is 4200mAh / g and 990mAh / g, respectively, and the working potential is relatively low. However, the charge and discharge process of silicon and tin after pulverization and stratification in the lithium alloy system undergoes huge volume changes, which far limits the capacity and cycle life of the material. According to reports by a large number of researchers, many methods have been used to overcome this defect, such as nanocrystallization of silicon or tin-based materials (such as nanopores, fiberization, nanosheets or foams), composites of carbonaceous materials, composites of metal materials and their metal oxides, etc. have been developed to solve the defects of silicon and tin negative electrodes.
[0003] Patent CN117976859 introduces a lithium-ion battery negative electrode material and its preparation method, wherein MoO3 hollow nanorods are dispersed in a carbon source solution and reacted; after the reaction, solid-liquid separation is performed, the solid phase is dried, and then the solid phase is calcined to obtain a calcined material; the calcined material is dispersed in deionized water, and ammonia water is added to obtain hollow nanorods; tin source and hollow nanorods are added to deionized water, dispersed, and then a hydrothermal reaction is performed; after the reaction, solid-liquid separation is performed to obtain a solid phase; the solid phase is dried, and then the solid phase is calcined to obtain a leaf-leaf-shaped negative electrode material, the leaf structure of which gives it good ductility and stability, good conductivity, and effectively alleviates the volume expansion during the use of the battery, thereby increasing the battery capacity. The first cycle capacity of the material obtained by this method is about 2.5 times that of the graphite negative electrode, but the capacity after 50 cycles is less than 500mAh / g, indicating that the cycle stability of the obtained leaf-leaf-shaped negative electrode material is limited. Summary of the invention
[0004] In order to solve the shortcomings of the prior art that the silicon-tin composite material has a large volume change, poor mechanical strength, and high charge transfer resistance, and the obtained lithium-ion battery cannot take into account excellent cycle performance, capacity, and rate performance, the present invention provides a silicon-tin composite material and a preparation method, application, and lithium-ion battery. The silicon-tin composite material has a small volume change, good mechanical strength, and low charge transfer resistance. The lithium-ion battery using it as a negative electrode material can take into account excellent cycle performance, capacity, and rate performance.
[0005] To achieve the above objectives, the present invention adopts the following technical solutions.
[0006] The present invention provides a silicon-tin composite material, which includes a core-shell structure, and the core-shell structure includes a core, an inner coating carbon layer and an outer coating carbon layer from the inside to the outside, wherein the core includes silicon material and tin nanoparticles; and the outer coating carbon layer is a chestnut-shaped carbon layer.
[0007] In the present invention, the silicon material includes but is not limited to silicon powder, and may also be silicon dioxide silicon powder.
[0008] In the present invention, the silicon material is preferably a porous silicon material, such as a mesoporous silicon material, wherein "mesoporous silicon material" means that the pore size of the silicon material is between 2 nm and 50 nm.
[0009] In the present invention, the D50 particle size of the tin nanoparticles may be 45-100 nm, preferably 60-100 nm.
[0010] In the present invention, preferably, the thickness of the inner coating carbon layer is greater than the thickness of the outer coating carbon layer.
[0011] In the present invention, the inner coating carbon layer preferably further includes heteroatoms, such as one or more of nitrogen, boron and phosphorus.
[0012] In the present invention, the outer carbon coating layer preferably further includes heteroatoms, such as one or more of nitrogen, boron and phosphorus.
[0013] In the present invention, a graphene layer is preferably provided outside the outer carbon coating layer.
[0014] In the present invention, the D50 particle size of the silicon-tin composite material may be 60-150 nm, preferably 90-130 nm, for example, 95 nm, 100 nm, 110 nm, 115 nm, 120 nm or 125 nm.
[0015] In the present invention, the pore size of the silicon-tin composite material may be 10-30 nm, preferably 12-24 nm, for example, 12.6 nm, 15.8 nm, 16.3 nm, 16.9 nm, 17.1 nm, 17.8 nm, 18.3 nm, 18.7 nm, 19.3 nm, 19.5 nm, 20.8 nm, 20.9 nm, 21.7 nm, 21.8 nm, 22.3 nm, 22.6 nm, 22.8 nm or 23.6 nm.
[0016] In the present invention, the silicon content in the silicon-tin composite material can be 40%-52%, preferably 43%-51%, for example, 43.3%, 43.9%, 44.1%, 44.6%, 44.8%, 45.2%, 45.4%, 45.8%, 46.1%, 46.3%, 46.5%, 46.7%, 46.8%, 47.3%, 47.7%, 48.1%, 48.5%, 48.7% or 50.1%, where the percentage is the mass percentage of silicon element in the silicon-tin composite material.
[0017] In the present invention, the tin content in the silicon-tin composite material can be 25%-36%, preferably 26%-32%, for example, 26.5%, 27%, 27.1%, 27.2%, 27.3%, 27.6%, 27.9%, 28.1%, 28.2%, 28.3%, 28.6%, 28.9%, 29.1%, 29.4%, 29.9%, 30.8% or 31.8%, where the percentage is the mass percentage of tin element in the silicon-tin composite material.
[0018] In the present invention, the carbon content in the silicon-tin composite material can be 16%-30%, preferably 19%-26%, for example, 19.3%, 19.4%, 19.5%, 19.9%, 20.7%, 21.6%, 21.8%, 22.5%, 22.7%, 22.8%, 23.1%, 23.8%, 24.3%, 24.8%, 24.9% or 25.1%, where the percentage is the mass percentage of carbon element in the silicon-tin composite material.
[0019] In the present invention, the nitrogen content in the silicon-tin composite material can be 0.02%-1.1%, preferably 0.05%-1.05%, for example 0.07%, 0.08%, 0.09%, 1%, 1.01% or 1.02%, where the percentage is the mass percentage of nitrogen in the silicon-tin composite material.
[0020] In the present invention, the boron content in the silicon-tin composite material may be 0.02%-1.1%, preferably 0.05%-1.05%, for example 0.09%, where the percentage is the mass percentage of the boron element in the silicon-tin composite material.
[0021] In the present invention, the phosphorus content in the silicon-tin composite material may be 0.02%-1.1%, preferably 0.05%-1.05%, where the percentage is the mass percentage of phosphorus element in the silicon-tin composite material.
[0022] In the present invention, the oxygen content in the silicon-tin composite material can be 1.5%-3.5%, preferably 1.8%-3.2%, for example, 1.89%, 1.92%, 1.98%, 2.09%, 2.12%, 2.16%, 2.35%, 2.38%, 2.41%, 2.45%, 2.46%, 2.61%, 2.68%, 2.83%, 2.91%, 3.01%, 3.07%, 3.09% or 3.12%, where the percentage is the mass percentage of oxygen element in the silicon-tin composite material.
[0023] In the present invention, the mass ratio of the silicon material to the tin nanoparticles is preferably (5-7):(3-5), for example, 7:4 or 7:5.
[0024] In the present invention, the electrical conductivity of the silicon-tin composite material can be (2.2-2.5)×10 4 S / m, for example, is 2.286×10 4 S / m, 2.289×10 4 S / m, 2.291×10 4 S / m, 2.294×10 4 S / m, 2.296×10 4 S / m, 2.297×10 4 S / m, 2.299×10 4 S / m, 2.300×10 4 S / m, 2.301×10 4 S / m, 2.302×10 4 S / m, 2.312×10 4 S / m, 2.313×10 4 S / m, 2.319×10 4 S / m, 2.346×10 4 S / m, 2.351×10 4 S / m, 2.371×10 4 S / m, 2.389×10 4 S / m or 2.396×10 4 S / m.
[0025] In the present invention, the charge transfer resistance of the silicon-tin composite material may be 15-30Ω, for example, 16.7Ω, 17.8Ω, 17.9Ω, 18.5Ω, 18.9Ω, 19.4Ω, 19.5Ω, 19.7Ω, 20.2Ω, 20.5Ω, 20.7Ω, 20.8Ω, 21.2Ω, 21.6Ω, 22.5Ω, 23.1Ω, 24.2Ω or 29.7Ω.
[0026] The present invention provides a method for preparing a silicon-tin composite material, which comprises the following steps:
[0027] S1, mixing a silicon source and a tin source to obtain a first precursor;
[0028] S2, coating the surface of the first precursor with a carbon layer, and forming tin nanoparticles from the tin source during the formation of the carbon layer, to obtain a second precursor;
[0029] S3. Coating a chestnut-shaped carbon layer on the surface of the second precursor.
[0030] In step S1, the mixing is preferably performed by ball milling.
[0031] The ball milling treatment is preferably carried out using a ball mill. Preferably, the ball mill tube volume of the ball mill is, for example, 0.2L.
[0032] The ball-to-material ratio of the ball milling treatment is preferably (30-50):1.
[0033] Wherein, the ball milling speed of the ball milling treatment is preferably 550-800r / min.
[0034] Wherein, the ball milling time of the ball milling treatment is preferably 6-10 hours.
[0035] Preferably, the ball milling process is a plasma-assisted ball milling process.
[0036] Wherein, the plasma-assisted ball milling process refers to an inert gas plasma formed by an inert gas under an inert atmosphere such as an inert gas. When the ball milling process is performed, the plasma will strongly sputter out some atoms on the surface of the abrasive. These atoms will enter the plasma and react with the inert gas atoms and molecules to form gaseous and solid compounds and substances. At the same time, the energy of the plasma will also eject many ions and electrons, and these particles will further process the surface of the abrasive. The plasma-assisted ball milling process is generally carried out under an inert atmosphere. Preferably, the inert atmosphere includes an inert gas and / or nitrogen. The inert gas can be selected from one or more of helium, argon and neon. The nitrogen is, for example, high-purity nitrogen.
[0037] Preferably, the working current of the plasma-assisted ball milling process is 1-3 A. Preferably, the excitation voltage of the plasma-assisted ball milling process is 10-25 kV. Preferably, the pressure of the inert atmosphere is 0.1 MPa, which corresponds to the gauge pressure.
[0038] In step S1, the mass ratio of the silicon source to the tin source is preferably (5-7):(3-5), for example, 7:4 or 7:5.
[0039] In step S1, the silicon source preferably includes silicon powder and / or silicon dioxide powder.
[0040] In step S1, the D50 particle size of the silicon source is preferably 50-100 nm, for example, 75 nm.
[0041] In step S1, the tin source preferably includes tin powder and / or tin dioxide powder.
[0042] In step S1, the D50 particle size of the tin source is preferably 30-100 nm, for example, 60 nm.
[0043] In the present invention, in step S2, the method for coating the carbon layer can be conventional in the art, preferably a solvent gel method.
[0044] In some preferred embodiments of the present invention, in step S2, coating the surface of the first precursor with a carbon layer by a solvent gel method comprises the following steps:
[0045] S2-1, ultrasonically dispersing the surfactant in water to form spherical micelles;
[0046] S2-2, adding a carbon source monomer and an alkali catalyst, stirring, and obtaining a sol;
[0047] S2-3, adding the first precursor to obtain a core-shell colloid;
[0048] S2-4, heating and polymerizing to obtain a first precursor coated with a gel polymer;
[0049] S2-5, carbonization, the gel polymer forms a carbon layer, and the tin source forms tin nanoparticles to obtain a second precursor.
[0050] In step S2-1, the molar ratio of the surfactant to the water is preferably (0.2-0.65): (3000-10000).
[0051] In step S2-1, the surfactant preferably includes one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide.
[0052] In steps S2-1 and S2-3, the molar ratio of the surfactant to the first precursor is preferably (0.2-0.65): (0.8-1.5).
[0053] In step S2-2, the carbon source monomer preferably includes a phenolic compound and an aldehyde compound. The phenolic compound is preferably resorcinol; the aldehyde compound is preferably formaldehyde. Preferably, the molar ratio of the phenolic compound, the aldehyde compound and the alkaline catalyst is (0.5-1.5): (500-1500): (0.007-0.03).
[0054] In step S2-2, the alkaline catalyst is preferably one or more of sodium carbonate, sodium hydroxide and sodium citrate.
[0055] In step S2-2, a heteroatom compound is preferably added before adding the carbon source monomer. Preferably, the molar ratio of the heteroatom compound to the first precursor is (0.01-0.09): (0.8-1.5). Preferably, the heteroatom compound includes one or more of a nitrogen source, a boron source and a phosphorus source. Among them, the nitrogen source can be selected from one or more of p-nitroaniline, melamine, triethylamine, pyridine, azobisethylbutyronitrile and pyrrole. The boron source can be selected from one or more of boric acid, triethyl borate and tripropyl borate. The phosphorus source can be selected from one or more of phytic acid, phosphoric acid and diammonium hydrogen phosphate.
[0056] In step S2-4, the temperature of the heating polymerization is preferably 80-100°C, for example 85°C.
[0057] In step S2-4, the heating polymerization time is preferably 2-6 hours, for example, 3 hours.
[0058] In step S2-5, the carbonization may be a conventional carbonization treatment step in the art. Preferably, the carbonization temperature is 650-950° C., for example, 700° C. Preferably, the carbonization time is 2-6 hours, for example, 4 hours.
[0059] In step S2-5, the carbonization is preferably carried out under an inert atmosphere. The inert atmosphere preferably includes an inert gas and / or nitrogen. The inert gas may be selected from one or more of helium, argon and neon. Preferably, the nitrogen is high-purity nitrogen.
[0060] In step S2-5, the carbonization preferably includes drying, which is preferably one or more of freeze drying, CO2 supercritical drying and vacuum drying.
[0061] In step S2-5, the carbonization preferably includes washing and drying. Preferably, the washing is carried out with water and ethanol. The drying is preferably one or more of freeze drying, CO2 supercritical drying and vacuum drying.
[0062] In the present invention, in step S3, a chemical bath deposition method and a solvent gel method are preferably used to coat the chestnut-shaped carbon layer on the surface of the second precursor.
[0063] In some preferred embodiments of the present invention, in step S3, a chestnut-shaped carbon layer is coated on the surface of the second precursor by a chemical bath deposition method and a solvent gel method, comprising the following steps:
[0064] S3-1, ultrasonically dispersing the second precursor in a quaternary ammonium salt aqueous solution to obtain a second precursor dispersion; adding an aqueous solution containing a nickel salt and an initiator to the second precursor dispersion, stirring, adding ammonia water, reacting under stirring, centrifuging, and drying to obtain a composite material A;
[0065] S3-2, performing a first carbonization on the composite material A to obtain a composite material B;
[0066] S3-3, adding the composite material B to a surfactant aqueous solution, and sequentially adding a carbon source monomer and an initiator, reacting under stirring, and centrifuging, washing and drying to obtain a composite material C;
[0067] S3-4, performing a second carbonization on the composite material C to obtain a composite material D; the composite material D comprises a nickel layer and a carbon layer;
[0068] S3-5. The composite material D is subjected to acid treatment to remove the nickel layer, and then washed and dried to form a chestnut-shaped carbon layer.
[0069] In step S3-1, the nickel salt may be a nickel salt commonly used in the art, for example, one or more selected from nickel acetate, nickel nitrate and nickel sulfate.
[0070] In step S3-1, the initiator may be an initiator commonly used in the art, for example, one or more selected from potassium persulfate, sodium persulfate, potassium hydrogen persulfate and ammonium persulfate.
[0071] In step S3-1, in the aqueous solution containing nickel salt and initiator, the concentration of the nickel salt is preferably 2-10 mg / mL.
[0072] In step S3-1, in the aqueous solution containing nickel salt and initiator, the concentration of the initiator is preferably 0.4-2 mg / mL.
[0073] In step S3-1, the mass fraction of the ammonia water is preferably 1%-20%, such as 1.5% or 10%. Preferably, the amount of ammonia water added is 15-25 mL.
[0074] In step S3-1, the stirring temperature is, for example, 25°C.
[0075] In step S3-1, the stirring time is preferably 25-55 min, for example 40 min.
[0076] In step S3-1, the drying is preferably vacuum drying. Preferably, the vacuum drying time is 4-8 hours, for example, 6 hours. Preferably, the vacuum drying temperature is 60-80°C.
[0077] In step S3-1, the quaternary ammonium salt in the quaternary ammonium salt aqueous solution may be a quaternary ammonium salt conventionally used in the art, for example, one or more selected from hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide.
[0078] In step S3-1, the mass ratio of the second precursor to the quaternary ammonium salt in the quaternary ammonium salt aqueous solution is preferably (0.3-1): (0.009-0.05).
[0079] In step S3-1, the concentration of the quaternary ammonium salt aqueous solution is preferably 0.18-1 mg / mL.
[0080] In step S3-1, the ultrasonic dispersion time is preferably 20-50 min.
[0081] In step S3-2, the first carbonization may be a carbonization treatment step conventionally used in the art; wherein the temperature of the first carbonization is preferably 350-600°C, for example 450°C. The time of the first carbonization is preferably 2-5h, for example 4h; preferably, the heating rate to the first carbonization temperature is preferably 1-10°C / min, for example 3°C / min.
[0082] In step S3-2, the first carbonization is preferably carried out under an inert atmosphere. The inert atmosphere preferably includes an inert gas and / or nitrogen. The inert gas can be selected from one or more of helium, neon and argon. The nitrogen is preferably high-purity nitrogen.
[0083] In step S3-3, the surfactant is preferably an anionic surfactant, wherein the anionic surfactant can be selected from one or more of sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium p-toluenesulfonate, sodium dodecylsulfonate and sodium α-olefinsulfonate.
[0084] In step S3-3, the concentration of the surfactant aqueous solution is preferably 12-40 mg / L, for example 32 mg / L.
[0085] In step S3-3, the mass ratio of the composite material B to the surfactant in the surfactant aqueous solution is preferably 1:(0.03-0.1), for example, 1:0.08.
[0086] In step S3-3, the initiator preferably includes one or more of potassium persulfate, sodium persulfate, potassium hydrogen persulfate and ammonium persulfate.
[0087] In step S3-3, the initiator is preferably an aqueous initiator solution. Preferably, the concentration of the aqueous initiator solution is preferably 6-16.5 mg / mL, for example 8.5 mg / mL.
[0088] In step S3-3, the mass ratio of the composite material B to the initiator is preferably 1:(2.5-6.5), for example, 1:3.4.
[0089] In step S3-3, before adding the carbon source monomer, a heteroatom compound is also added. Wherein, the mass ratio of the heteroatom compound to the composite material B is, for example, 1.9:1. Preferably, the heteroatom compound includes one or more of a nitrogen source, a boron source and a phosphorus source. Wherein, the nitrogen source is preferably selected from one or more of p-nitroaniline, melamine, triethylamine, pyridine, azobisethylbutyronitrile and pyrrole, for example, pyrrole. The boron source is preferably selected from one or more of boric acid, triethyl borate and tripropyl borate. The phosphorus source is preferably selected from one or more of phytic acid, phosphoric acid and diammonium hydrogen phosphate.
[0090] Preferably, the process further comprises stirring after adding the heteroatom compound. Preferably, the stirring time is 25-55 minutes, for example, 40 minutes. Preferably, the stirring temperature is 0-5°C, for example, 2°C.
[0091] In step S3-3, the reaction temperature is preferably below 5°C, for example, 3°C.
[0092] In step S3-3, the reaction time is, for example, 24 hours.
[0093] In step S3-3, the detergent used for washing is preferably water and / or ethanol.
[0094] In step S3-3, the drying is preferably vacuum drying. Preferably, the temperature of the vacuum drying is 60-80°C; preferably, the time of the vacuum drying is 10-20 hours, for example, 16 hours.
[0095] In step S3-4, the second carbonization can be a carbonization treatment step conventionally used in the art, wherein the temperature of the second carbonization is preferably 650-850°C, for example 700°C, and the time of the second carbonization is preferably 3-6h, for example 5h.
[0096] In step S3-5, the acid treatment may be an acid treatment step used in the art. Preferably, the acid used in the acid treatment may be selected from one or more of hydrochloric acid, nitric acid and sulfuric acid. Preferably, the concentration of the acid is preferably 3-10 mol / L, for example, 5 mol / L or 8 mol / L.
[0097] In step S3-5, the washing detergent is preferably water.
[0098] In step S3-5, the drying is preferably vacuum drying; the temperature of the vacuum drying is preferably 60-80°C; and the time of the vacuum drying is preferably 15-24h, for example 16h.
[0099] In the present invention, preferably, step S3 further comprises step S4: coating the surface of the composite material obtained in step S3 with a graphene layer.
[0100] The graphene layer may be coated by a coating method conventionally used in the art. Preferably, the surface of the composite material obtained in step S3 is coated with a graphene layer, comprising the following steps:
[0101] S4-1, adding the composite material obtained in step S3 and humic acid into water to obtain a premix, and adding an ammonia solution under stirring;
[0102] S4-2, heating, sintering treatment, cooling;
[0103] S4-3, carbonization, graphene is formed in situ after thermal decomposition of humic acid.
[0104] In step S4-1, the humic acid is preferably humic acid powder.
[0105] In step S4-1, the mass ratio of the composite material obtained in step S3 to the humic acid is preferably (9-12): (0.8-1.5).
[0106] In step S4-1, the solid-to-liquid ratio of the premix is preferably 1:(10-15), for example, 1:10.
[0107] In step S4-1, the mass concentration of the aqueous ammonia solution is preferably 10%-30%, for example, 15%, 20% or 28%.
[0108] In step S4-1, the amount of the aqueous ammonia solution used is preferably such that the humic acid is completely dissolved.
[0109] In step S4-1, the ammonia solution is preferably added dropwise, and preferably, the rate of the addition is 0.1-0.45 mL / min, for example, 0.25 mL / min.
[0110] In step S4-2, the heating temperature is preferably 80-100°C, for example, 90°C.
[0111] In step S4-2, the heating time is preferably 20-24 hours.
[0112] In step S4-2, the sintering temperature is preferably 200-300°C, for example, 280°C.
[0113] In step S4-2, the sintering time is preferably 1-3 hours, for example 2 hours.
[0114] In step S4-2, the sintering is preferably performed in a microwave oven.
[0115] In step S4-3, the carbonization temperature is preferably 500-850° C., for example, 800° C. Preferably, the heating rate to the carbonization temperature is 1-10° C. / min, for example, 3° C. / min.
[0116] In step S4-3, the carbonization time is preferably 8-15 hours, for example 10 hours.
[0117] In step S4-3, the carbonization is preferably performed in a tubular furnace.
[0118] In step S4-3, the carbonization is preferably carried out in an inert atmosphere. The inert atmosphere preferably includes an inert gas and / or nitrogen. The inert gas can be selected from one or more of helium, neon and argon. Preferably, the nitrogen is high-purity nitrogen.
[0119] In the present invention, the drying may be a drying method conventionally used in the art, preferably one or more of freeze drying, CO2 supercritical drying and vacuum drying.
[0120] In some specific embodiments, the drying is freeze drying; the freeze drying temperature is preferably -30°C to -80°C; and the freeze drying time is preferably 1-5h.
[0121] In some specific embodiments, the drying is CO2 supercritical drying; the temperature of the CO2 supercritical drying is preferably 10-40°C; the pressure of the CO2 supercritical drying is preferably 10-15kPa; and the time of the CO2 supercritical drying is preferably 1-3h.
[0122] In some specific embodiments, the drying is vacuum drying; the temperature of the vacuum drying is preferably 60-90°C, for example 80°C; the time of the vacuum drying is preferably 4-24h, for example 6h, 15h or 16h.
[0123] The present invention provides a silicon-tin composite material, which is prepared by the above-mentioned method for preparing the silicon-tin composite material.
[0124] The present invention provides an application of the silicon-tin composite material as a negative electrode material in a lithium ion battery.
[0125] The present invention also provides a lithium ion battery, which adopts the silicon-tin composite material as described above.
[0126] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0127] The reagents and raw materials used in the present invention are commercially available.
[0128] The positive and progressive effects of the present invention are:
[0129] The core of the silicon-tin composite material of the present invention includes silicon material and tin nanoparticles, and an inner coating carbon layer and an outer coating carbon layer are sequentially arranged outside the core from the inside to the outside, wherein the outer coating carbon layer is a chestnut-shaped carbon layer. The silicon-tin composite material has low charge transfer resistance, good electrical conductivity, and good mechanical strength. It can alleviate the stress change of volume expansion of the silicon-tin alloy during charging and discharging and ensure the stability of its electronic conductivity, increase the lithium ion transmission pathway, and enhance the lithium ion deintercalation speed; the lithium ion battery containing it can take into account excellent cycle performance, capacity and rate performance. In particular, when the inner coating carbon layer and the outer coating carbon layer are doped with heteroatoms, the synergistic effect inside and outside the carbon layer can also be enhanced, further improving the electrochemical performance of the lithium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0130] Figure 1 Schematic diagram of the structure of the silicon-tin composite material obtained in Examples 1-20 and 22.
[0131] Figure 2 Schematic diagram of the structure of the silicon-tin composite material obtained in Example 21.
[0132] Figure 3 This is a test diagram of the cycle performance of the lithium-ion battery obtained in Example 1.
[0133] Figure 4 This is a rate performance test diagram of the lithium ion battery obtained in Example 1.
[0134] Reference numerals:
[0135] Tin nanoparticles 1
[0136] Silicon material 2
[0137] Inner carbon coating 3
[0138] Chestnut-shaped carbon layer 4
[0139] Graphene layer 5 DETAILED DESCRIPTION
[0140] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0141] The main reagents used in the following examples and comparative examples are as follows:
[0142] Hexadecyltrimethylammonium bromide, analytical grade, was purchased from Shanghai Aoxing Pharmaceutical Technology Equipment Co., Ltd.;
[0143] Pyridine was purchased from Wujiang Huaxu Chemical Technology Co., Ltd.;
[0144] Resorcinol and formaldehyde were of analytical grade and purchased from Sinopharm Group;
[0145] Hydrochloric acid, analytical grade, was purchased from Sinopharm Group;
[0146] Sodium carbonate, analytical grade, was purchased from Wanhua Chemical Co., Ltd.;
[0147] Alkyl dimethyl benzyl ammonium bromide, analytical grade, was purchased from Hangzhou Jessica Chemical Co., Ltd.;
[0148] Nickel acetate, analytical grade, was purchased from Sinopharm Group;
[0149] Potassium persulfate, analytical grade, was purchased from Wanhua Chemical;
[0150] Pyrrole, analytical grade, was purchased from Wanhua Chemical.
[0151] Example 1
[0152] (1) Preparation of silicon-tin composite material:
[0153] S1. Preparation of the first precursor:
[0154] Silicon powder (D50 particle size is 75nm) and tin powder (D50 particle size is 60nm) are placed in a ball mill at a mass ratio of 7:4 for plasma-assisted ball milling. Vacuum sealing grease is applied to the rubber ring of the end cover of the ball mill and the rubber ring of the electrode rod shoulder, and the ball mill is packaged. The ball mill is evacuated through a vacuum valve, and then filled with argon gas with a gauge pressure of 0.1MPa, and repeated 3 times, and finally the environmental condition in the ball mill is an inert gas of about 0.1MPa. Among them, the ball-to-material ratio is 50:1, the ball mill speed is 650r / min, the ball mill time is 8h, and the ball mill tube volume is 0.2L. The working current is 1-3A, the excitation voltage is 10-25kV, and the first precursor is efficiently synthesized and uniformly obtained through the synergistic effect of inert gas plasma and grinding balls.
[0155] S2. A carbon layer is coated on the surface of the first precursor by a solvent gel method to prepare a second precursor:
[0156] S2-1. Hexadecyltrimethylammonium bromide (0.35 mmol) and deionized water (8 mol) were mixed, and the mixture was uniformly mixed by ultrasonic dispersion to form spherical micelles for fixation.
[0157] S2-2. Add a mixture of 0.04 mmol pyridine, resorcinol (0.8 mmol), formaldehyde (0.8 mol) and 0.009 mmol sodium carbonate, and continue stirring to obtain a surface-stabilized sol.
[0158] S2-3, adding 1.2 mmol of the first precursor to obtain a surfactant-stabilized core-shell colloid.
[0159] S2-4, then the core-shell colloid is polymerized at 85° C. (polymerization time is 3 h) to obtain a first precursor coated with a gel polymer.
[0160] S2-5. After drying, heat treatment is performed at 700°C for 4 hours in an argon atmosphere to carbonize the gel polymer. Then, the gel polymer is repeatedly rinsed with water and ethanol, and vacuum dried at 80°C for 15 hours to obtain the second precursor (in this process, the tin powder forms tin nanoparticles).
[0161] S3, using chemical bath deposition method and solvent gel method to coat the chestnut-shaped carbon layer on the surface of the second precursor:
[0162] S3-1. Add 0.5 g of the second precursor into 50 mL of deionized water dissolved with 0.02 g of hexadecyltrimethylammonium bromide, stir, and perform ultrasonic treatment for 20-50 min to obtain a second precursor dispersion.
[0163] Dissolve 0.1g of nickel acetate and 0.02g of initiator potassium persulfate in another 50mL of distilled water. After complete dissolution, slowly add to the second precursor dispersion. After stirring for 40min, add 20mL of 1.5% ammonia water. Stir for another 50min at 25°C in an oil bath. Finally, collect the product by centrifugation and vacuum dry at 80°C for 6h to obtain composite material A.
[0164] S3-2. Composite material A is then heat treated under argon conditions: heated to 450° C. at a heating rate of 3° C. / min and kept at a constant temperature for 4 hours to obtain composite material B.
[0165] S3-3, dissolve 8 mg of sodium dodecylbenzene sulfonate in 250 mL of deionized water. Add 0.1 g of composite material B and stir for 40 min; add 0.2 mL of pyrrole (0.19 g) in an ice bath at 2 ° C and stir for 40 min. At the same time, dissolve 0.34 g of initiator potassium persulfate in 40 mL of distilled water. After complete dissolution, add to the pyrrole mixed solution and stir at a reaction temperature of 3 ° C for 24 h. At the end of the reaction, collect the product by centrifugation, wash with distilled water and ethanol in turn to remove impurities, and vacuum dry at 80 ° C for 16 h to obtain composite material C.
[0166] S3-4. Heat-treat the composite material C in an argon atmosphere at 700° C. for 5 h to obtain a composite material D (including a nickel layer and a carbon layer).
[0167] S3-5, 5 mol / L hydrochloric acid and composite material D were mixed, filtered, and the material was washed with deionized water to neutrality. Finally, vacuum dried at 80° C. for 16 h to form a chestnut-shaped carbon layer, thereby obtaining a silicon-tin composite material.
[0168] (2) Preparation of lithium-ion batteries:
[0169] The silicon-tin composite material prepared as the negative electrode material was mixed with a conductive agent (KS-6), a binder carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 95.5:1.5:1.5:1.5 (a total of 100 g), added into 300 mL of water, and mixed evenly to obtain a negative electrode slurry, which was applied on a copper foil with a compaction density of 1.60 g / cm 3 , and used as the negative electrode after vacuum drying; lithium metal is used as the counter electrode; the solute in the electrolyte is LiPF6, the solvent is ethylene carbonate (EC) and dimethyl carbonate (DMC) (mass ratio is 1:1), the concentration of the electrolyte is 1 mol / L; the separator is PE / PP / PE composite film, and it can be assembled into a button battery.
[0170] Example 2
[0171] The difference between this embodiment and embodiment 1 is that in the preparation of the silicon-tin composite material, silicon dioxide powder is used to replace silicon powder in step S1, and the other conditions are consistent with those in embodiment 1.
[0172] Example 3
[0173] The difference between this embodiment and embodiment 1 is that in the preparation of the silicon-tin composite material, the mass ratio of silicon powder to tin powder in step S1 is 7:5, and the other conditions are consistent with those in embodiment 1.
[0174] Example 4
[0175] The difference between this embodiment and embodiment 1 is that in the preparation of the silicon-tin composite material, the amount of hexadecyltrimethylammonium bromide used in step S2-1 is 0.40 mmol, and the other conditions are consistent with those in embodiment 1.
[0176] Example 5
[0177] The difference between this embodiment and embodiment 1 is that in the preparation of the silicon-tin composite material, triethylamine is used to replace pyridine in step S2-2, and the other conditions are consistent with those in embodiment 1.
[0178] Example 6
[0179] The difference between this embodiment and embodiment 1 is that in the preparation of the silicon-tin composite material, the amount of pyridine used in step S2-2 is 0.05 mmol, and the other conditions are consistent with those in embodiment 1.
[0180] Example 7
[0181] The difference between this embodiment and embodiment 1 is that in the preparation of the silicon-tin composite material, the polymerization time in step S2-4 is 5 hours, and the other conditions are consistent with those in embodiment 1.
[0182] Example 8
[0183] The difference between this embodiment and embodiment 1 is that in the preparation of the silicon-tin composite material, dialkyldimethylammonium chloride is used in step S2-1 to replace hexadecyltrimethylammonium bromide, and the other conditions are consistent with those in embodiment 1.
[0184] Example 9
[0185] The difference between this embodiment and embodiment 1 is that in the preparation of the silicon-tin composite material, all drying is performed by freeze drying instead of vacuum drying, the freeze drying temperature is -60°C, the freeze drying time is 2 hours, and the other conditions are consistent with those in embodiment 1.
[0186] Example 10
[0187] The difference between this embodiment and embodiment 1 is that in the preparation of the silicon-tin composite material, the amount of the first precursor in step S2-3 is 1.5 mmol, and the other conditions are consistent with those in embodiment 1.
[0188] Embodiment 11
[0189] The difference between this embodiment and embodiment 1 is that in the preparation of the silicon-tin composite material, the temperature of the heat treatment in step S2-5 is 750° C., and the other conditions are consistent with those in embodiment 1.
[0190] Example 12
[0191] The difference between this embodiment and embodiment 1 is that in the preparation of the silicon-tin composite material, alkyl dimethyl benzyl ammonium bromide is used in step S3-1 to replace hexadecyl trimethyl ammonium bromide, and the other conditions are consistent with those in embodiment 1.
[0192] Embodiment 13
[0193] The difference between this embodiment and embodiment 1 is that in the preparation of the silicon-tin composite material, all drying is replaced by CO2 supercritical drying, the temperature is 20°C, the pressure is 10 kPa, the drying time is 1.5 h, and the other conditions are consistent with embodiment 1.
[0194] Embodiment 14
[0195] The difference between this embodiment and embodiment 1 is that in the preparation of the silicon-tin composite material, the initiator in the chemical bath deposition of nickel in step S3-1 is potassium persulfate, and the other conditions are consistent with those in embodiment 1.
[0196] Embodiment 15
[0197] The difference between this embodiment and embodiment 1 is that in the preparation of the silicon-tin composite material, hexadecyltrimethylammonium p-toluenesulfonate is used in step S3-3 to replace sodium dodecylbenzenesulfonate, and the other conditions are consistent with those in embodiment 1.
[0198] Example 16
[0199] The difference between this embodiment and embodiment 1 is that in the preparation of the silicon-tin composite material, pyridine is used to replace pyrrole in step S3-3, and the other conditions are consistent with those in embodiment 1.
[0200] Embodiment 17
[0201] The difference between this embodiment and embodiment 1 is that in the preparation of the silicon-tin composite material, the heat treatment temperature in step S3-2 is 550°C, and the other conditions are consistent with those in embodiment 1.
[0202] Embodiment 18
[0203] The difference between this embodiment and embodiment 1 is that in the preparation of the silicon-tin composite material, nitric acid is used instead of hydrochloric acid in step S3-5, and the other conditions are consistent with those in embodiment 1.
[0204] Embodiment 19
[0205] The difference between this embodiment and embodiment 1 is that in the preparation of the silicon-tin composite material, pyridine is not used in step S2-2 and pyrrole is not used in step S3-3, and the other conditions are consistent with those in embodiment 1.
[0206] Embodiment 20
[0207] The difference between this embodiment and embodiment 1 is that in the preparation of the silicon-tin composite material, boric acid is used to replace pyridine in step S2-2, and boric acid is used to replace pyrrole in step S3-3, and the other conditions are consistent with those in embodiment 1.
[0208] Embodiment 21
[0209] The difference between this embodiment and embodiment 1 is that the preparation of the silicon-tin composite material further includes step S4 (the surface of the composite material obtained in step S3 in embodiment 1 is coated with a graphene layer):
[0210] 5 g of the composite material obtained in step S3 of Example 1 and 0.5 g of humic acid powder (mass ratio of 10:1) are added to deionized water and mixed evenly, and the solid-liquid ratio is controlled at 1:10. Then, an ammonia solution with a concentration of 28 wt% is added dropwise under stirring until the humic acid powder is completely dissolved (dropping rate is 5 mL / min), and then the temperature is raised to 90° C. and the solvent is evaporated at a constant temperature to make the humic acid uniformly coat the surface of the composite material obtained in step S3. The composite material is placed in a microwave oven at a temperature of 280° C. for sintering for 2 h, then cooled and taken out, and then placed in an inert atmosphere in a tubular furnace and heated at a rate of 3° C. / min and a temperature of 800° C. for 10 h to obtain a silicon-tin composite material with a graphene layer coated on the outer surface.
[0211] The remaining conditions remain the same as in Example 1.
[0212] Embodiment 22
[0213] The difference between this embodiment and embodiment 1 is that in the preparation of the silicon-tin composite material, a chemical vapor deposition method is used instead of step S1-2. The specific steps of the chemical vapor deposition method are as follows:
[0214] The silicon-tin material precursor was heated to 300° C. at a heating rate of 5° C. / min in a nitrogen atmosphere and kept at that temperature for 2 h.
[0215] The remaining conditions remain the same as in Example 1.
[0216] In Examples 1-22, the D50 particle size of the tin nanoparticles in the obtained silicon-tin composite material is 45-100 nm. The schematic diagram of the structure of the silicon-tin composite material obtained in Examples 1-20 and 22 is as follows: Figure 1 As shown, the silicon-tin composite material includes a core (including silicon material 2 and tin nanoparticles 1), an inner carbon coating layer 3 and an outer carbon coating layer (i.e., a chestnut-shaped carbon layer 4) from the inside to the outside. The structural schematic diagram of the silicon-tin composite material obtained in Example 21 is shown in Figure 2 As shown, the silicon-tin composite material includes, from the inside to the outside, a core (including silicon material 2 and tin nanoparticles 1), an inner coating carbon layer 3, an outer coating carbon layer (i.e., a chestnut-shaped carbon layer 4) and a graphene layer 5.
[0217] Comparative Example 1
[0218] The difference between this comparative example and Example 1 is that in the preparation of the lithium-ion battery, silicon powder is used to replace the silicon-tin composite material as the negative electrode material, and the other conditions are consistent with Example 1.
[0219] Comparative Example 2
[0220] The difference between this comparative example and Example 1 is that in the preparation of the lithium-ion battery, tin powder is used to replace the silicon-tin composite material as the negative electrode material, and the other conditions are consistent with Example 1.
[0221] Comparative Example 3
[0222] The difference between this comparative example and Example 1 is that in the preparation of the silicon-tin composite material, there is no step S3, and the other conditions are the same as those in Example 1.
[0223] Comparative Example 4
[0224] The difference between this comparative example and Example 1 is that in the preparation of the silicon-tin composite material, in step S1, no tin powder is used, but only silicon powder is used, and the other conditions are the same as those in Example 1.
[0225] Comparative Example 5
[0226] The difference between this comparative example and Example 1 is that in the preparation of the silicon-tin composite material, in step S1, no silicon powder is used, but only tin powder is used, and the other conditions are the same as those in Example 1.
[0227] Comparative Example 6
[0228] The difference between this comparative example and Example 1 is that in the preparation of the silicon-tin composite material, nickel acetate is not used in step S3-1, and there is no step S3-5, the obtained outer coating carbon layer is not a chestnut-shaped structure, and the other conditions are consistent with Example 1.
[0229] Comparative Example 7
[0230] The difference between this comparative example and Example 1 is that in the preparation of the silicon-tin composite material, there is no step S2, that is, the obtained silicon-tin composite material has no inner coating carbon layer, and the other conditions are consistent with Example 1.
[0231] Effect Example 1
[0232] The silicon-tin composite materials prepared in Examples 1-22 and the negative electrode materials in Comparative Examples 1-7 were tested for element content, D50 particle size, conductivity, pore size and charge transfer resistance:
[0233] The element content was tested by XRF (pre-treatment of the silicon-tin composite material was performed by microwave digestion): 2±0.05g of stearic acid and 6±0.5g of silicon-tin composite material were mixed and ground, pressed into tablets, and then heated in Avio TM The test was conducted in a 200 device; the test conditions: the air pressure was greater than 2MPa. The D50 particle size was measured by a laser particle size diffractometer (Malvern 3000) at room temperature for 1 minute by ultrasonic testing; the conductivity was measured by Orion Star TM The conductivity was measured by A212 benchtop conductivity meter at room temperature. The pore size was measured by POROLUX Cito instrument. The above test results are shown in Table 1.
[0234] Effect Example 2
[0235] The lithium ion batteries prepared in Examples 1-22 and Comparative Examples 1-7 were subjected to the following performance tests using a Wuhan Blue Power Xinwei 5v / 10mA battery tester:
[0236] (1) First discharge specific capacity and 200 cycle capacity at 0.1C
[0237] At 25°C, the rate charge and discharge were performed at a current density of 0.1C-2C, and the charging voltage was limited to 0.005-2V. The test results are shown in Table 2. The cycle performance test diagram of the lithium ion battery in Example 1 is shown in Table 2. Figure 3 shown.
[0238] (2) Rate performance
[0239] The test results of the rate performance at a rate of 0.1C for 200 cycles are shown in Table 3. Figure 4 shown.
[0240] Table 1
[0241]
[0242]
[0243] Table 2
[0244]
[0245]
[0246] Table 3
[0247] serial number 0.1C / 0.1C 0.2C / 0.1C 0.5C / 0.1C 1C / 0.1C 2C / 0.1C 0.1C / 0.1C Example 1 2332.8 2165.7 2013.6 1805.6 1649.7 2319.4 Embodiment 19 2337.9 2134.8 1969.3 1774.6 1610.9 2316.7 Embodiment 21 2340.2 2197.6 2057.1 1849.3 1703.7 2331.5 Comparative Example 1 4188.8 3109 2409 1920 1290 3678 Comparative Example 2 990.6 754 690 540 304 897 Comparative Example 3 2344.8 2108 1899 1678 1389 2300 Comparative Example 4 3263.8 2869 2657 2432 2109 3109 Comparative Example 5 824.9 760 659 489 297 789 Comparative Example 6 2331.2 2165 1997 1768 1568 2289 Comparative Example 7 2689.6 2308 2032 1830 1534 2511
[0248] Note: “ / ” in Table 1 means that the condition parameter is not involved in the specific experiment.
[0249] The silicon-tin composite material in Examples 1-22 of the present invention contains a core-shell structure with silicon material and tin nanoparticles as the core and an inner coating carbon layer and a chestnut-shaped carbon layer as the outer coating carbon layer as the shell. This special structure can form multiple protections so that the volume expansion of the silicon material and the tin nanoparticles is limitedly alleviated, the charge transfer resistance is low, and the resulting lithium-ion battery has excellent rate performance, and can take into account excellent first coulomb efficiency, first discharge specific capacity and cycle capacity.
[0250] Compared with Example 1, Comparative Example 1-2 directly uses silicon powder or tin powder as the negative electrode material, and the charge transfer resistance of the material is significantly improved. Although the initial discharge specific capacity of the obtained lithium-ion battery is relatively high, the 200-cycle capacity at 0.1C is significantly reduced, and the initial coulomb efficiency is greatly reduced, even less than 70%, and the rate performance is also significantly deteriorated. This may be because when silicon powder or tin powder is used alone as the negative electrode material, the volume expansion is serious, which is very unfavorable to the electrochemical performance of the battery.
[0251] Compared with Example 1, the silicon-tin composite material obtained in Comparative Example 3 does not have a chestnut-shaped carbon layer as an outer coating layer, but only has one carbon layer as a coating layer. The charge transfer resistance of the material is significantly improved. Although the first discharge specific capacity of the obtained lithium-ion battery is high, the 200-cycle capacity at 0.1C is significantly reduced, and the first coulombic efficiency is also reduced, and the rate performance is also poor. This may be because when the composite material is used as a negative electrode material, only one carbon layer as a coating layer cannot effectively alleviate the volume expansion, thereby failing to effectively improve the electrochemical performance of the battery.
[0252] Compared with Example 1, in the core-shell structure of the composite material obtained in Comparative Example 4, the core is only tin nanoparticles obtained by using a single tin powder, rather than a silicon-tin composite, and the charge transfer resistance of the material is greatly improved. Although the first discharge specific capacity and 200 cycle capacity at 0.1C of the obtained lithium-ion battery are high and the rate performance is good, the first coulombic efficiency is significantly reduced, which is only 90.3%.
[0253] Compared with Example 1, in the core-shell structure of the composite material obtained in Comparative Example 5, the core is only a silicon material obtained by using a single silicon powder, rather than a silicon-tin composite. The charge transfer resistance of the material is significantly improved. Although the first coulombic efficiency of the obtained lithium-ion battery is high, the first discharge specific capacity and the 200-cycle capacity at 0.1C are greatly reduced, and the rate performance is significantly deteriorated.
[0254] Compared with Example 1, nickel acetate (template) was not used in Comparative Example 6, and the outer carbon layer obtained was not a chestnut-shaped structure. Although the first coulombic efficiency, first discharge specific capacity and 200 cycle capacity at 0.1C of the obtained lithium-ion battery were basically the same, the rate performance was significantly worse. This may be because the outer carbon layer with a chestnut-shaped structure in Example 1 significantly enhanced the diffusion of lithium ions, which was conducive to improving the rate performance.
[0255] Compared with Example 1, in Comparative Example 7, there is no silicon-tin composite material and no inner coating carbon layer. Although the initial discharge specific capacity and 200 cycle capacity at 0.1C of the obtained lithium-ion battery are relatively high, the initial coulombic efficiency and rate performance are significantly deteriorated. This may be because the inner coating carbon layer combined with the outer coating carbon layer with a chestnut-shaped structure is conducive to inhibiting volume expansion, and the outer coating carbon layer alone cannot effectively inhibit volume expansion.
[0256] The doped carbon layer in Example 1 effectively alleviates the volume expansion of silicon and tin materials and further improves the electronic conductivity. Compared with Example 1, Example 19 does not dope nitrogen in the inner and outer carbon layers. Although the charge transfer resistance is improved and the rate performance is reduced, it is still within the excellent range. The obtained lithium-ion battery can still take into account the excellent first coulomb efficiency, first discharge specific capacity, cycle capacity and rate performance.
[0257] On the basis of Example 1, in Example 21, a graphene layer is further provided outside the outer carbon layer of the silicon-tin composite material, and the lithium-ion battery obtained by using the obtained silicon-tin composite material as the negative electrode material has a high first discharge specific capacity and cycle capacity, a high first coulombic efficiency, and excellent rate performance. This may be because the additionally provided graphene layer as the outer surface of the composite material is conducive to further improving the mechanical stability of the material, further inhibiting the volume expansion of silicon and tin, and contributing a certain amount of additional capacity.
[0258] The inner coating carbon layer of the silicon-tin composite material in Example 22 is prepared by chemical vapor deposition. Compared with the silicon-tin composite material prepared by the solvent gel method in Example 1, although the first coulombic efficiency of the obtained lithium-ion battery is reduced, it is also relatively excellent, and it can also take into account excellent first discharge specific capacity and cycle capacity.
[0259] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A silicon-tin composite material, characterized in that: The silicon-tin composite material includes a core-shell structure, which includes a core, an inner coating carbon layer and an outer coating carbon layer from the inside to the outside, wherein the core includes silicon material and tin nanoparticles; and the outer coating carbon layer is a chestnut-shaped carbon layer.
2. The silicon-tin composite material according to claim 1, characterized in that It meets one or more of the following conditions: a. The silicon material is a porous silicon material, such as a mesoporous silicon material; b. The D50 particle size of the tin nanoparticles is 45-100 nm, preferably 60-100 nm; c. The thickness of the inner carbon coating layer is greater than the thickness of the outer carbon coating layer; d. the inner carbon coating layer further includes heteroatoms, such as one or more of nitrogen, boron and phosphorus; e. The outer carbon coating layer further includes heteroatoms, such as one or more of nitrogen, boron and phosphorus; f. A graphene layer is further provided outside the outer carbon coating layer; g. The D50 particle size of the silicon-tin composite material is 60-150 nm, preferably 90-130 nm, for example, 95 nm, 100 nm, 110 nm, 115 nm, 120 nm or 125 nm; h. The pore size of the silicon-tin composite material is 10-30 nm, preferably 12-24 nm, for example, 12.6 nm, 15.8 nm, 16.3 nm, 16.9 nm, 17.1 nm, 17.8 nm, 18.3 nm, 18.7 nm, 19.3 nm, 19.5 nm, 20.8 nm, 20.9 nm, 21.7 nm, 21.8 nm, 22.3 nm, 22.6 nm, 22.8 nm or 23.6 nm.
3. The silicon-tin composite material according to claim 1, characterized in that: It satisfies one or more of the following conditions aj: a. The silicon content of the silicon-tin composite material is 40%-52%, preferably 43%-51%, for example, 43.3%, 43.9%, 44.1%, 44.6%, 44.8%, 45.2%, 45.4%, 45.8%, 46.1%, 46.3%, 46.5%, 46.7%, 46.8%, 47.3%, 47.7%, 48.1%, 48.5%, 48.7% or 50.1%, where the percentage is the mass percentage of silicon element in the silicon-tin composite material; b. The tin content of the silicon-tin composite material is 25%-36%, preferably 26%-32%, for example, 26.5%, 27%, 27.1%, 27.2%, 27.3%, 27.6%, 27.9%, 28.1%, 28.2%, 28.3%, 28.6%, 28.9%, 29.1%, 29.4%, 29.9%, 30.8% or 31.8%, where the percentage is the mass percentage of the tin element in the silicon-tin composite material; c. The carbon content of the silicon-tin composite material is 16%-30%, preferably 19%-26%, for example, 19.3%, 19.4%, 19.5%, 19.9%, 20.7%, 21.6%, 21.8%, 22.5%, 22.7%, 22.8%, 23.1%, 23.8%, 24.3%, 24.8%, 24.9% or 25.1%, where the percentage is the mass percentage of carbon element in the silicon-tin composite material; d. The nitrogen content in the silicon-tin composite material is 0.02%-1.1%, preferably 0.05%-1.05%, for example 0.07%, 0.08%, 0.09%, 1%, 1.01% or 1.02%, where the percentage is the mass percentage of nitrogen in the silicon-tin composite material; e. The boron content in the silicon-tin composite material is 0.02%-1.1%, preferably 0.05%-1.05%, for example 0.09%, where the percentage is the mass percentage of the boron element in the silicon-tin composite material; f. The phosphorus content in the silicon-tin composite material is 0.02%-1.1%, preferably 0.05%-1.05%, where the percentage is the mass percentage of phosphorus in the silicon-tin composite material; g. The oxygen content of the silicon-tin composite material is 1.5%-3.5%, preferably 1.8%-3.2%, for example, 1.89%, 1.92%, 1.98%, 2.09%, 2.12%, 2.16%, 2.35%, 2.38%, 2.41%, 2.45%, 2.46%, 2.61%, 2.68%, 2.83%, 2.91%, 3.01%, 3.07%, 3.09% or 3.12%, where the percentage is the mass percentage of oxygen element in the silicon-tin composite material; h. The mass ratio of the silicon material to the tin nanoparticles is (5-7):(3-5), for example, 7:4 or 7:5; i. The electrical conductivity of the silicon-tin composite material is (2.2-2.5)×10 4 S / m, for example, is 2.286×10 4 S / m, 2.289×10 4 S / m, 2.291×10 4 S / m, 2.294×10 4 S / m, 2.296×10 4 S / m, 2.297×10 4 S / m, 2.299×10 4 S / m, 2.300×10 4 S / m, 2.301×10 4 S / m, 2.302×10 4 S / m, 2.312×10 4 S / m, 2.313×10 4 S / m, 2.319×10 4 S / m, 2.346×10 4 S / m, 2.351×10 4 S / m, 2.371×10 4 S / m, 2.389×10 4 S / m or 2.396×10 4 S / m; j. The charge transfer resistance of the silicon-tin composite material is 15-30Ω, for example, 16.7Ω, 17.8Ω, 17.9Ω, 18.5Ω, 18.9Ω, 19.4Ω, 19.5Ω, 19.7Ω, 20.2Ω, 20.5Ω, 20.7Ω, 20.8Ω, 21.2Ω, 21.6Ω, 22.5Ω, 23.1Ω, 24.2Ω or 29.7Ω.
4. A method for preparing a silicon-tin composite material, characterized in that: It includes the following steps: S1, mixing a silicon source and a tin source to obtain a first precursor; S2, coating the surface of the first precursor with a carbon layer, and forming tin nanoparticles from the tin source during the formation of the carbon layer, to obtain a second precursor; S3. Coating a chestnut-shaped carbon layer on the surface of the second precursor.
5. The method for preparing the silicon-tin composite material according to claim 4, characterized in that: Step S1 satisfies one or more of the following conditions af: a. In step S1, the mixing is performed by ball milling; The ball milling treatment is preferably carried out by a ball mill; the ball milling tube volume of the ball mill is, for example, 0.2 L; the ball-to-material ratio of the ball milling treatment is preferably (30-50):1; the ball milling speed of the ball milling treatment is preferably 550-800 r / min; the ball milling time of the ball milling treatment is preferably 6-10 h; Preferably, the ball milling process is a plasma-assisted ball milling process; preferably, the working current of the plasma-assisted ball milling process is 1-3A; preferably, the excitation voltage of the plasma-assisted ball milling process is 10-25kV; preferably, the plasma-assisted ball milling process is generally carried out under an inert atmosphere; preferably, the inert atmosphere includes an inert gas and / or nitrogen; preferably, the inert gas is selected from one or more of helium, argon and neon; the nitrogen is, for example, high-purity nitrogen; preferably, the pressure of the inert atmosphere is 0.1MPa; b. In step S1, the mass ratio of the silicon source to the tin source is (5-7):(3-5), for example, 7:4 or 7:5; c. In step S1, the silicon source includes silicon powder and / or silicon dioxide powder; d. In step S1, the D50 particle size of the silicon source is 50-100 nm, for example, 75 nm; e. In step S1, the tin source includes tin powder and / or tin dioxide powder; f. In step S1, the D50 particle size of the tin source is 30-100 nm, for example, 60 nm.
6. The method for preparing the silicon-tin composite material according to claim 4, characterized in that: In step S2, a carbon layer is coated on the surface of the first precursor by a solvent gel method, comprising the following steps: S2-1, ultrasonically dispersing the surfactant in water to form spherical micelles; S2-2, adding a carbon source monomer and an alkali catalyst, stirring, and obtaining a sol; S2-3, adding the first precursor to obtain a core-shell colloid; S2-4, heating and polymerizing to obtain a first precursor coated with a gel polymer; S2-5, carbonization, the gel polymer forms a carbon layer, and the tin source forms tin nanoparticles to obtain a second precursor; Wherein, in step S2-1, the molar ratio of the surfactant to the water is preferably (0.2-0.65): (3000-10000); Wherein, in step S2-1, the surfactant preferably includes one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide; Wherein, in steps S2-1 and S2-3, the molar ratio of the surfactant to the first precursor is preferably (0.2-0.65): (0.8-1.5); Wherein, in step S2-2, the carbon source monomer preferably includes a phenolic compound and an aldehyde compound; wherein the phenolic compound is preferably resorcinol; the aldehyde compound is preferably formaldehyde; preferably, the molar ratio of the phenolic compound, the aldehyde compound and the base catalyst is (0.5-1.5): (500-1500): (0.007-0.03); Wherein, in step S2-2, the alkaline catalyst is preferably one or more of sodium carbonate, sodium hydroxide and sodium citrate; Wherein, in step S2-2, a heteroatom compound is preferably added before adding the carbon source monomer; preferably, the molar ratio of the heteroatom compound to the first precursor is (0.01-0.09): (0.8-1.5); preferably, the heteroatom compound includes one or more of a nitrogen source, a boron source and a phosphorus source; wherein the nitrogen source is preferably selected from one or more of p-nitroaniline, melamine, triethylamine, pyridine, azobisethylbutyronitrile and pyrrole; the boron source is preferably selected from one or more of boric acid, triethyl borate and tripropyl borate; the phosphorus source is preferably selected from one or more of phytic acid, phosphoric acid and diammonium hydrogen phosphate; Wherein, in step S2-4, the temperature of the heating polymerization is preferably 80-100°C, for example, 85°C; Wherein, in step S2-4, the heating polymerization time is preferably 2-6 hours, for example, 3 hours; In step S2-5, preferably, the carbonization temperature is 650-950°C, for example, 700°C; preferably, the carbonization time is 2-6h, for example, 4h; Wherein, in step S2-5, the carbonization is preferably carried out under an inert atmosphere; wherein the inert atmosphere preferably includes an inert gas and / or nitrogen; the inert gas is preferably selected from one or more of helium, argon and neon; the nitrogen is, for example, high-purity nitrogen; Wherein, in step S2-5, the carbonization preferably further includes drying; the drying is preferably one or more of freeze drying, CO2 supercritical drying and vacuum drying; Wherein, in step S2-5, the carbonization preferably further includes washing and drying; preferably, the washing uses water and ethanol; the drying is preferably one or more of freeze drying, CO2 supercritical drying and vacuum drying.
7. The method for preparing the silicon-tin composite material according to claim 4, characterized in that: Step S3 satisfies one or both of the following conditions ab: a. In step S3, a chestnut-shaped carbon layer is coated on the surface of the second precursor by a chemical bath deposition method and a solvent gel method, comprising the following steps: S3-1, ultrasonically dispersing the second precursor in a quaternary ammonium salt aqueous solution to obtain a second precursor dispersion; adding an aqueous solution containing a nickel salt and an initiator to the second precursor dispersion, stirring, adding ammonia water, reacting under stirring, centrifuging, and drying to obtain a composite material A; S3-2, performing a first carbonization on the composite material A to obtain a composite material B; S3-3, adding the composite material B to a surfactant aqueous solution, and sequentially adding a carbon source monomer and an initiator, reacting under stirring, and centrifuging, washing and drying to obtain a composite material C; S3-4, performing a second carbonization on the composite material C to obtain a composite material D; the composite material D comprises a nickel layer and a carbon layer; S3-5, treating the composite material D with acid to remove the nickel layer, washing, and drying to form a chestnut-shaped carbon layer; Wherein, in step S3-1, the nickel salt is preferably selected from one or more of nickel acetate, nickel nitrate and nickel sulfate; Wherein, in step S3-1, the initiator is preferably selected from one or more of potassium persulfate, sodium persulfate, potassium hydrogen persulfate and ammonium persulfate; Wherein, in step S3-1, in the aqueous solution containing nickel salt and initiator, the concentration of the nickel salt is preferably 2-10 mg / mL; the concentration of the initiator is preferably 0.4-2 mg / mL; Wherein, in step S3-1, the mass fraction of the ammonia water is preferably 10%-20%, for example, 1.5%; preferably, the amount of the ammonia water added is 15-25 mL; Wherein, in step S3-1, the stirring temperature is, for example, 25°C; the stirring time is preferably 25-55 minutes, for example, 40 minutes; Wherein, in step S3-1, the drying is preferably vacuum drying; preferably, the vacuum drying time is 4-8 hours, for example, 6 hours; preferably, the vacuum drying temperature is 60-80°C; Wherein, in step S3-1, the quaternary ammonium salt in the quaternary ammonium salt aqueous solution is preferably selected from one or more of hexadecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, dialkyldimethylammonium chloride and alkyldimethylbenzylammonium bromide; Wherein, in step S3-1, the mass ratio of the second precursor to the quaternary ammonium salt in the quaternary ammonium salt aqueous solution is preferably (0.3-1): (0.009-0.05); Wherein, in step S3-1, the concentration of the quaternary ammonium salt aqueous solution is preferably 0.18-1 mg / mL; Wherein, in step S3-1, the ultrasonic dispersion time is preferably 20-50 min; Wherein, in step S3-2, the temperature of the first carbonization is preferably 350-600°C, for example, 450°C; the time of the first carbonization is preferably 2-5h, for example, 4h; preferably, the heating rate to the first carbonization temperature is preferably 1-10°C / min, for example, 3°C / min; Wherein, in step S3-2, the first carbonization is preferably carried out under an inert atmosphere; the inert atmosphere preferably includes an inert gas and / or nitrogen; the inert gas is preferably selected from one or more of helium, neon and argon; the nitrogen is, for example, high-purity nitrogen; Wherein, in step S3-3, the surfactant is preferably an anionic surfactant; preferably, the anionic surfactant is selected from one or more of sodium dodecylbenzenesulfonate, hexadecyltrimethylammonium p-toluenesulfonate, sodium dodecylsulfonate and sodium α-olefinsulfonate; Wherein, in step S3-3, the concentration of the surfactant aqueous solution is preferably 12-40 mg / L, for example, 32 mg / L; Wherein, in step S3-3, the initiator preferably includes one or more of potassium persulfate, sodium persulfate, potassium hydrogen persulfate and ammonium persulfate; Wherein, in step S3-3, the initiator is preferably an initiator aqueous solution; preferably, the concentration of the initiator aqueous solution is preferably 6-16.5 mg / mL, for example, 8.5 mg / mL; In step S3-3, the mass ratio of the composite material B to the initiator is preferably 1:(2.5-6.5), for example, 1:3.4; Wherein, in step S3-3, before adding the carbon source monomer, a heteroatom compound is also added; wherein the mass ratio of the heteroatom compound to the composite material B is, for example, 1.9:1; preferably, the heteroatom compound includes one or more of a nitrogen source, a boron source and a phosphorus source; wherein the nitrogen source is preferably selected from one or more of p-nitroaniline, melamine, triethylamine, pyridine, azobisethylbutyronitrile and pyrrole, for example, pyrrole; the boron source is preferably selected from one or more of boric acid, triethyl borate and tripropyl borate; the phosphorus source is preferably selected from one or more of phytic acid, phosphoric acid and diammonium hydrogen phosphate; Preferably, the step of adding the heteroatom compound further includes stirring; preferably, the stirring time is 25-55 minutes, for example, 40 minutes; preferably, the stirring temperature is 0-5°C, for example, 2°C; Wherein, in step S3-3, the reaction temperature is preferably lower than 5°C, for example, 3°C; Wherein, in step S3-3, the reaction time is, for example, 24 hours; Wherein, in step S3-3, the washing agent used for washing is preferably water and / or ethanol; Wherein, in step S3-3, the drying is preferably vacuum drying; preferably, the temperature of the vacuum drying is 60-80°C; preferably, the time of the vacuum drying is 10-20h, for example, 16h; Wherein, in step S3-4, the temperature of the second carbonization is preferably 650-850°C, for example, 700°C; the time of the second carbonization is preferably 3-6h, for example, 5h; Wherein, in step S3-5, preferably, the acid used in the acid treatment is selected from one or more of hydrochloric acid, nitric acid and sulfuric acid; preferably, the concentration of the acid is preferably 3-10 mol / L, for example, 5 mol / L or 8 mol / L; Wherein, in step S3-5, the washing detergent is preferably water; Wherein, in step S3-5, the drying is preferably vacuum drying; the temperature of the vacuum drying is preferably 60-80° C.; the time of the vacuum drying is preferably 15-24 hours, for example 16 hours; b. After step S3, the step further includes step S4: coating the surface of the composite material obtained in step S3 with a graphene layer; Preferably, the method comprises the following steps: S4-1, adding the composite material obtained in step S3 and humic acid into water to obtain a premix, and adding an ammonia solution under stirring; S4-2, heating, sintering treatment, cooling; S4-3, carbonization, in-situ formation of graphene after thermal decomposition of humic acid; Wherein, in step S4-1, the humic acid is preferably humic acid powder; Wherein, in step S4-1, the mass ratio of the composite material obtained in step S3 to the humic acid is preferably (9-12): (0.8-1.5); Wherein, in step S4-1, the solid-liquid ratio of the premix is preferably 1:(10-15), for example, 1:10; Wherein, in step S4-1, the mass concentration of the aqueous ammonia solution is preferably 10%-30%, for example, 15%, 20% or 28%; the amount of the aqueous ammonia solution is preferably such that the humic acid is completely dissolved; Wherein, in step S4-1, the method of adding the ammonia solution is preferably dropwise addition; preferably, the rate of the dropwise addition is 0.1-0.45 mL / min, for example, 0.25 mL / min; Wherein, in step S4-2, the heating temperature is preferably 80-100° C., for example, 90° C.; the heating time is preferably 20-24 hours; Wherein, in step S4-2, the sintering temperature is preferably 200-300°C, for example, 280°C; the sintering time is preferably 1-3h, for example, 2h; and the sintering is preferably performed in a microwave oven; Wherein, in step S4-3, the carbonization temperature is preferably 500-850°C, for example, 800°C; preferably, the heating rate to the carbonization temperature is 1-10°C / min, for example, 3°C / min; the carbonization time is preferably 8-15h, for example, 10h; the carbonization is preferably carried out in a tubular furnace; Among them, in step S4-3, the carbonization is preferably carried out in an inert atmosphere; the inert atmosphere preferably includes an inert gas and / or nitrogen; the inert gas is preferably selected from one or more of helium, neon and argon; the nitrogen is, for example, high-purity nitrogen.
8. A silicon-tin composite material, characterized in that: The silicon-tin composite material is prepared by the preparation method of any one of claims 4 to 7.
9. Use of the silicon-tin composite material according to any one of claims 1 to 3 and 8 as a negative electrode material in a lithium ion battery.
10. A lithium ion battery, characterized in that: It adopts the silicon-tin composite material as described in any one of claims 1-3 and 8.